Immediate effects of forefoot wedges on multi-segment foot kinematics during jogging in recreational runners with a symptomatic pronated foot - Zhang, Xianyi; Vanwanseele, Benedicte (Frontiers in Physiology, 2023)
Foot orthoses (FOs) have been used to alter lower limb kinematics and kinetics in pronated feet. A clear relationship between FOs’ features, e.g., the amount of wedging and support, and the corresponding biomechanical responses is vital for the design and prescription of FOs. In this study, we sought to determine if changing the level of the forefoot wedge would cause a linear response in the multi-segment foot kinematics during jogging, and if this effect would be enhanced by an arch support. Ten pairs of 3D printed FOs with five levels of forefoot wedges and two levels of arch supports were tested on 12 recreational runners with a symptomatic pronated foot. Multi-segment foot kinematic data during jogging was measured using the Oxford Foot Model. Two-way ANOVAs were performed to examine the main effect of the forefoot wedge and arch support, as well as their interaction on peak joint angles. Statistical parametric mapping and paired-t tests were used to identify differences in the foot kinematic traces and the joint range of motion (ROM) between each FO and the control, respectively. Linear main effects for the forefoot wedge level were found in the forefoot peak dorsiflexion, eversion and rearfoot peak dorsiflexion of jogging. FOs with a medial forefoot wedge caused an average of 2.5° reduction of the forefoot peak abduction during jogging. Furthermore, forefoot wedges showed an opposite effect on the sagittal ROM of the forefoot and rearfoot. Adding an arch support did not improve the kinematic performance of a forefoot wedge during jogging. This study highlights a linear dose-response effect of a forefoot wedge on forefoot kinematics, and suggests using a medial forefoot wedge as an anti-pronator component for controlling forefoot motion of a pronated foot.